The Survival and Treatment of Fusarium oxysporum f. sp. cubense in Water - Sahabne Ullah; Diane Mostert; Kobus Serfontein; Altus Viljoen (Journal of Fungi, 2021)
Fusarium oxysporum f. sp cubense (Foc), the causal agent of Fusarium wilt, is one of the most devastating constraints to banana production worldwide. The spread of Foc in water is particularly concerning, as infested water can rapidly contaminate disease-free areas. The objectives of this study were to investigate the survival of Foc in water and to test the effectiveness of water treatment with chlorine, ozone, UV, and peracetic acid. The study indicated that Foc spores can survive in water for more than 120 days, but that viability was reduced in stagnant water, probably due to anaerobic conditions when spores settled at the bottom. It is therefore recommended that surface water be extracted and treated before it is used for irrigation. The efficacy of all water treatments was reduced in the presence of soil, implying that water needs to be soil-free before treatment. The use of peracetic acid is recommended to treat Foc-contaminated water, as it is safe for use and does not require installation costs although it is effective at treating Foc-contaminated water, ozone would require significant input costs and chlorine can produce harmful disinfection by-products. UV would be impractical for field application because of the high doses required to eliminate Foc.